THE EFFECT OF COMPENSATION ON THE WORK PRODUCTIVITY OF SENAMAS ENERGINDO MINERAL EMPLOYES IN EAST BARITO - Ahmad Farhani (stiatabalong.ac.id, 2024)
Increased productivity, which was carried out by the company for employees as a means of perfecting the human resource through the creation of motivation, is one of the factors that can directly influence employee productivity, and one way to motivate employees to increase the productivity of their work is by awarding appropriate compensation from the company. The purpose of this research is to find out and analyze the effect of compensation on employee productivity at PT. Senamas Energindo Mineral in Barito Timur. The research method used to use quantitative methods with a simple linear analysis tool with free variables is variable compensation and work productivity. Sample techniques used in this research were random sampling. Population: 627 employees of PT. Senamas Energindo Minerals, which samples as many as 86 employees. Based on the results of the research note that the positive effect of compensation against work productivity with the R Square of 0.353, meaning that contributions to the compensation effect on work productivity of 35.3% and the rest of 64.7% is affected by other variables. The implications of the research are that further internal research needs to be carried out by the company PT. Senamas Energindo Mineral in East Barito in terms of reviewing efforts to increase or maintain the level of employee work productivity at a level that is in line with the company's expectations to support the company's efforts in achieving its goals. Keywords: Compensation, Work Productivity, Employee, Company